A systematic review and meta-analysis of the association between arterial carbon dioxide tension and outcomes after cardiac arrest. (February 2017) - McKenzie, Nicole; Williams, Teresa A.; Tohira, Hideo; Ho, Kwok M.; Finn, Judith
Abstract: Introduction: Arterial carbon dioxide tension (PaCO2 ) abnormalities are common after cardiac arrest (CA). Maintaining a normal PaCO2 makes physiological sense and is recommended as a therapeutic target after CA, but few studies have examined the association between PaCO2 and patient outcomes. This systematic review and meta-analysis aimed to assess the effect of a low or high PaCO2 on patient outcomes after CA. Methods: We searched MEDLINE, EMBASE, CINAHL and Cochrane CENTRAL, for studies that evaluated the association between PaCO2 and outcomes after CA. The primary outcome was hospital survival. Secondary outcomes included neurological status at the end of each study's follow up period, hospital discharge destination and 30-day survival. Meta-analysis was conducted if statistical heterogeneity was low. Results: The systematic review included nine studies; eight provided sufficient quantitative data for meta-analysis. Using PaCO2 cut-points of <35 mmHg and >45 mmHg to define hypo- and hypercarbia, normocarbia was associated with increased hospital survival (odds ratio [OR] 1.30, 95% confidence interval [CI] 1.23, 1.38). Normocarbia was also associated with a good neurological outcome (cerebral performance category score 1 or 2) compared to hypercarbia (OR 1.69, 95% CI 1.13, 2.51) when the analysis also included an additional study with a slightly different definition for normocarbia (PaCO2 30–50 mmHg). Conclusions: From the limited data it appears PaCO2 has an important U-shape association with survival and outcomes after CA, consistent with international resuscitation guidelines' recommendation that normocarbia be targeted during post-resuscitation care.